Agreement between International Center for Agricultural Research in the Dry Areas and Ethiopian Broadcasting Corporation - International Center for Agricultural Research in the Dry Areas; Ethiopian Broadcasting Corporation (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Mou-International Center for Agricultural Research in the Dry Areas and Ethiopian Broadcasting Corporation